Osteoconductivity of Bovine Xenograft Granules of Different Sizes in Sinus Lift: A Histomorphometric Study in Rabbits - Eduardo Pires Godoy; Karol Alí Apaza Alccayhuaman; Daniele Botticelli; Andrea Amaroli; Vitor Ferreira Balan; Erick Ricardo Silva; Samuel Porfirio Xavier (MDPI AG, 2021)
Background: Due to the lack of data on bone-to-graft contact (BGC) over time in the various regions within the subantral space of the augmented sinus floor, the present study aimed to evaluate the osteoconductivity of deproteinized bovine bone mineral (DBBM) with granules of different sizes applied in maxillary sinus floor elevation. Methods: A maxillary sinus augmentation was performed bilaterally in 18 rabbits using DBBM with particle dimensions of either 0.125-1.0 mm or 1-2 mm. The antrostomy was covered using a collagen barrier. The animals were euthanized in groups of six after 2, 4, and 8 weeks of healing. MicroCT and histological analyses were performed. Results: After 2 weeks of healing, BGC was 10.9% and 11.9% for the small and large granule sites, respectively. After 8 weeks of healing, the BGC increased to 65% and 62% at the small and large granule sites, respectively. The highest values were located close to the bony walls and the bony window. New bone content developed between 2 and 8 weeks from 7.0% to 27.6% and from 6.1% to 27.6% at the small and large granule sites, respectively. Conclusions: Similar outcomes in osteoconductivity and bone formation were found at both small and large DBBM granule sites.